A cross sectional study on risk factors associated with acute lower respiratory tract infection among children aged 6 to 60 months - Noorani, Tabrez Altaf; Kothari, Jaini S.; Kanabar, Bhavesh (International Journal of Contemporary Pediatrics, 2020)
Background: Acute lower respiratory tract infection (ALRI) is leading cause of hospitalization and mortality among children under 5 years age in developing societies. Risk factors such as socioeconomic status, overcrowding, parental education, passive smoking, exposure to biomass fuels, kerosene lamps etc should also be considered in possible etiology of ALRI. Knowledge of risk factors would help prevention through proper health education efforts and other interventional community development initiatives. The objective of the study was to study various socio-demographic and nutritional risk factors associated with acute lower respiratory tract infection among 6 to 60 months aged children Methods: This cross-sectional study was conducted in a tertiary care institute Gujarat state of India. All the children in the age group of 6 months to 60 months admitted in paediatrics ward with ALRI were included in study. Data collection was done using a pretested questionnaire including socio-demographic factors. Data was analyzed using Statistical package for social sciences (SPSS) and excel and p<0.05 was considered as statistically significant. Results: Higher percentage (32%) of malnutrition was observed in age group of 13 months to 36 months (p<0.05). Lack of maternal education is significantly associated with malnutrition in patients of acute lower respiratory tract infection (LRTI) (p<0.05). Passive smoking was found among 38.1% of ALRI patients in urban area while it was among 25.6% of patients in rural patients (p<0.05). Difference in exposure to biomass fuel among rural and urban patients is statistically significant (p<0.05). Giving pre-lacteal feeding (63.9%), incomplete immunization (56.8%), no birth spacing (50.2%), no predominant breast feeding (47.7%) are some of the leading causes of acute LRTI. Conclusion: Socio-demographic factors and malnutrition impact ALRI among 6 to 60 months age group of children according to place of residence.